BEHAVIORAL ARCHITECTURE FOR EARLY CHILDHOOD DEVELOPMENT: A CASE STUDY OF A KINDERGARTEN IN BATAM - Michel Aldinata; Carissa Dinar Aguspriyanti; Lathifa Nursyamsu (Program Sarjana Arsitektur Universitas Internasional Batam, 2025)
Early childhood represents a golden phase of human development, characterized by rapid growth across physical and motor, cognitive, language, social, and moral domains. While research on the influence of physical and non-physical environments on child development continues to expand, limited attention has been given to the systematic application of behavioral architecture in early childhood education settings that potentially support early childhood development. This study addresses this gap by examining the implementation of behavioral architecture principles at Christian Kalam Kudus 2 Kindergarten in Batam City, Indonesia. Using a qualitative approach that combined literature review, field observation, and semi-structured interviews. The study points out the implementation of five key elements of behavioral architecture that contribute to developmental outcomes. Spatial function and furniture (including their arrangement) emerged as the most influential factors, whereas spatial size and form, colour, and environmental conditions (sound, temperature, and lighting) provided partial contributions. Several design shortcomings were also identified, notably thermal discomfort and insufficient artificial lighting. Overall, the study emphasizes that kindergartens are not merely functional spaces but active agents in shaping behavior, learning processes, and development of young children through behavioral architecture that responds to user needs and environmental conditions.